Macromolecular Design of Hydroxyl Functional Linear and Star-Shaped L-Lactide and ?-Caprolactone Biodegradable Polyesters Utilizing Biosafe Catalysts for Biomedical Applications - Başalp, Dildare; Tıhmınlıoğlu, Funda (Izmir Institute of Technology, 2017)
In the present study, macromolecular design of homo and copolymers of lactide (LA) and ε-caprolactone (CL) in different structures by the use of biocompatible catalysts and co-initiators were performed to satisfy a need of tailor-made bioassimilable polymeric structures without any hazardous metal contaminants for various medical applications. Linear and star shaped (di, tetra and hexa functional) poly(L-lactide) (PLLA) and poly(ε-caprolactone) (PCL) homo/copolymers were synthesized by using bismuth(III)acetate (Bi(III)Ac) and creatinine as biosafe catalysts and ethylene glycol, pentaerythritol and myo-inositol as co-initiators. The effect of catalyst type on polymer properties was observed by differences in crystalline structure. Crystalline and amorphous linear and star shaped PLLAs were obtained by using Bi(III)Ac and creatinine as catalysts, respectively. The activity of creatinine was very low comparing to Bi(III)Ac and SnOct2 catalysts. The reactivity of LA monomer was found to be higher than that of CL monomer. The high molecular weight polymers having low PDI values were obtained by using Bi(III)Ac catalyst contary to creatinine catalyst. The decrease in glass transition temperatures and molecular weights of synthesized PLLA and PCL homo/copolymers were observed with the increase in amount of co-initiators due to the decrease in chain length and disruption of crystal formation. The cytotoxicity properties of the catalysts and synthesized linear and functional homo/co PLLAs and PCLs were carried out according to MTT assay. Cytotoxicity of Bi(III)Ac was found as lower than that of SnOct2. Creatinine and the synthesized polymers did not show any cytotoxic properties. The observation of no cytotoxic effect of creatinine catalyst results in the biosafe usage of creatinine catalyst instead of toxic SnOct2 for the synthesis of moderate or low molecular weight homo/co PLLAs and PCLs in bioapplications.

Bu çalışmada, farklı medikal uygulamalarda ihtiyaca yönelik biyo polimerik yapıların sağlanması için tehlikeli metal kontaminasyon içermeyen biyo uyumlu katalizörler ve yardımcı başlatıcılar kullanılarak L-laktid (LA) ve ...-kaprolakton (CL) homo ve kopolimerlerinin makromolekül dizaynı gerçekleştirilmiştir. Lineer ve yıldız şekilli (iki, dört ve altı hidroksi fonksiyonlu) poli(L-laktid) (PLLA), poli(...-kaprolakton) (PCL) homo/kopolimerleri biyo uyumlu bizmut(III)asetat (Bi(III)Ac) ve kreatinin katalizörleri ve yardımcı başlatıcı olarak etilen glikol, pentaeriltritol ve myo-inositol kullanılarak sentezlenmiştir. Sentezlenen polimerlerin kristal yapılarında katalizör çeşidinin etkisiyle farklılıklar gözlenmiştir. Kristal ve amorf yapıda linear ve yıldız şekilli PLLA’lar sırasıyla Bi(III)Ac ve kreatinin katalizörleri kullanılarak elde edilmiştir. Kreatinin aktivitesi Bi(III)Ac ve SnOct2 katalizörlerine göre oldukça düşüktür. LA monomerinin reaktivitesi CL monomerinin reaktivitesinden daha yüksek olduğu saptanmıştır. Yüksek molekül ağırlıklı ve düşük PDI değerlerine sahip polimerler kreatinin katalizörünün aksine Bi(III)Ac katalizörü kullanılarak elde edilmiştir. Kullanılan yardımcı başlatıcı miktarı arttıkça kristal yapı oluşumunun bozulması ve zincir uzunluğunun azalmasından dolayı, sentezlenen PLLA ve PCL homo/kopolimerlerinin camsı geçiş sıcaklıklarında ve molekül ağırlıklarında azalma gözlenmiştir. Katalizör ve sentezlenen linear ve fonksiyonel homo/ko PLLA ve PCL polimerlerinin sitotoksik özellikleri MTT test ile belirlenmiştir. Bi(III)Ac’nin sitotoksitesi SnOct2’ye göre daha düşük olduğu bulunmuştur. Kreatinin ve sentezlenen tüm polimerler herhangi bir sitotoksik etki göstermemiştir. Kreatinin katalizörünün sitotoksik etki göstermemesi, kreatinin biyo güvenli olarak toksik SnOct2 katalizörü yerine düşük ve ortalama molekül ağırlıklarında homo/ko PLLA ve PCL polimerlerinin sentezinde biyo uygulamalara yönelik kullanılabileceği sonucuna varılmıştır.
Hidroksi Fonksiyonlu Doğrusal ve Yıldız Şekilli L-laktid ve Ε-kaproloktan Biyobozunur Poliesterlerin Biyo Güvenli Katalizörler Kullanılarak Biyomedical Uygulamalara Yönelik Makromoleküler Dizaynı
Thesis (Doctoral)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2017
Full text release delayed at author's request until 2020.09.09
Includes bibliographical references (leaves: 139-167)
Text in English; Abstract: Turkish and English
Keywords: Cytotoxicity; Polylactide; ε-Caprolactone; Polymers; Biomedical applications; Biosafe catalysts